Stormwater Runoff Control Analysis Using Rain Garden Implementation in the Drainage System of GKB, Universitas Negeri Malang - Camila Aysha Putri Bachtiar; Vita Ayu Kusuma Dewi; Titi Rahayuningsih; Mega Septia Sarda Dewi (G-Tech: Jurnal Teknologi Terapan, 2025)
Climate change and rapid urbanization have intensified stormwater runoff in urban areas, including Malang City, while conventional drainage systems often lack the capacity to manage excess flow. This study aims to design and evaluate a rain garden model as a sustainable green infrastructure for reducing stormwater runoff in the GKB area of Universitas Negeri Malang, which frequently experiences inundation of up to 20 cm. The methodology involved rainfall analysis, probability distribution testing, and peak discharge estimation to determine the design parameters. The rain garden’s performance was assessed by comparing its storage capacity with the calculated runoff volume. Results indicate that for a two-year return period (0.134 m³/s), the proposed rain garden can fully accommodate runoff within its designed capacity. These findings demonstrate the potential of rain gardens as an effective nature-based solution to improve drainage efficiency and enhance urban flood resilience.